Whatsapp-Based Online Learning on Social Science Subjects for Fifth-Grade Students in MIN 9 Hulu Sungai Selatan - Noor Hidayati (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2021)
The current situation due to the covid-19 pandemic has forced all parties with various considerations to issue a policy. One of them is closing schools by replacing face-to-face with online learning. The purpose of the study was to determine whatsapp-based online learning in Social Studies subjects Class V at MIN 9 Hulu Sungai Selatan as well as the supporting and inhibiting factors of learning. Data collection techniques using in-depth interviews and documentation. Furthermore, it was analyzed descriptively qualitatively. The results of this study indicate that whatsapp-based online learning in social studies subject class V at MIN 9 Hulu Sungai Selatan has been running smoothly, it can be seen through the planning, implementation and evaluation stages of learning. Planning with the teacher to make an appropriate lesson plan. The implementation of learning begins with preliminary, core and closing activities. Learning evaluation is carried out through post-test either with assignments or tests. Supporting factors are efficient quotas, mastery of teacher technology and coordination of teachers and parents. The inhibiting factors for the unstable internet network, limited mastery of technology owned by parents, the difficulty of controlling in following lessons make teachers less aware of which students already understand and do not understand.